Simultaneous Estimation of Aflatoxins (B1, B2, G1 and G2) by Liquid Chromatography Coupled with Mass Spectrometry (LC-MS) in Corn Samples - Sailaja, O.; Manoranjani, M.; Krishnaveni, G. (Asian Journal of Chemistry, 2021)
Aflatoxins produced by Aspergillus flavins and Aspergillus pasasiticus have been investigated in the corn (maize) collected in different locations in Andhra Pradesh state, India. In the present study, 24 corn samples collected from different harvest, storage and dumping areas were analyzed for detection of aflatoxin contamination by liquid chromatography coupled with mass spectrometry (LC-MS). Mixed aflatoxin working standard solutions with a concentration of 10, 20, 30, 40, 50 and 60 ng/mL were prepared and followed by instrumental analysis and the retention times of the sample chromatograms were compared with the standard aflatoxins B1, B2, G1 and G2 retention times in order to determine the contamination. The findings revealed that among 24 collected samples, only 10 samples have been found positive for aflatoxins contamination when subjected to LC-MS analysis. Co-occurrence of aflatoxin was identified in the most of the samples. Even though 10 samples were tested positive total aflatoxin content in the most positive are found within the acceptable limits (30 μg/kg) and samples collected at dumping areas (S4, S8 and S10) show the presence of exceeding quantity than the limits described by FSSAI. Total aflatoxin content in the most positive were found within the acceptable limits (30 μg/kg) and the samples collected at dumping areas S4 (40.9 μg/kg), S8 (53.2 μg/kg) and S10 (71.86 μg/kg) had shown exceeding limits. The sample S7 collected from the storage was also found positive of presence of aflatoxin G2- 13.49 μg/kg and B2-21.14 μg/kg with total aflatoxin of 34.65 μg/kg. High contamination of these dumping areas may lead to contamination of storage points nearer to these areas. Present results showed that the corn samples at dumping areas were found to be contaminated with the Aspergillus flavins and Aspergillus pasasiticus.